A transgressão na adolescência: face à dificuldade de tornar-se homem, o apego à mãe - Elaine Rocha Maciel Carneiro (2017)
This dissertation is based on an observation extracted from professional experiences with adolescents who committed an infraction. Many of these had a strong attachment to their mothers. We extracted from there the hypothesis that there would be an articulation between adolescence, transgression and mother. This raised some questions: to what extent would transgression in adolescence be associated to the love to the mother? What place do these mothers occupy in the lives of their sons? Adolescence, transgression and mother constitute the threefold structure that forms the basis of our investigation. We started from elaborations that allowed us to locate transgression in adolescence as a historically situated construction and enabled the analysis of its incidence in a given context. We also discerned how transgression is approached in specific discourses. Our hypothesis called for a clinical investigation that approaches the adolescent to the mother/son relationship. Psychoanalysis proposes to us the construction of the masculine position and, inevitably, the separation of the maternal Other as a requirement of the moment of adolescence. Our theoretical elaborations and the analysis of the film "Standing tall" pointed us to the first difficulty of these adolescents: to become a man. They get attached to the mother as an outlet for the impossible that marks the sexual experience. This attachment can take place on the aspects of being or having. It was clarified thru the interviews with two adolescents under the socio educative measure of internment and their mothers. To approach them we used the methodology of Clinical Interviews of Psychoanalytic Orientation. In the first case, the adolescent is dedicated of being the object of maternal enjoyment, keeping fixed to the role of the child. Transgression sustains him in this place of object that hides the truth of the maternal symptom. In the second case, the adolescent occupies a position of the man to the mother by the way of the incestuous fantasy. Thru the transgression act he aims the having that would allow him to position himself in the virile dynamics. But this way keeps him captive of the maternal partnership, which leads him to support being the hero to his mother. The lack of a father's transmission or the disbelief in the father makes it difficult for the adolescent to become a man, which keeps him invested in the maternal partnership. He takes the transgression as the way to sustain himself in the position of being or having, as the film and the cases revealed to us.